2014
DOI: 10.1586/17474086.2014.963550
|View full text |Cite
|
Sign up to set email alerts
|

Design of the INHIBIT trial: preventing inhibitors by avoiding ‘danger’, prolonging half-life and promoting tolerance

Abstract: Inhibitor formation is among the most serious complications of hemophilia treatment. With the US FDA licensure of the novel long-lasting recombinant factor VIII (FVIII) Fc fusion protein, Eloctate, which prolongs FVIII half-life, we propose an innovative approach to prevent inhibitor formation. In this paper, we describe a multicenter, Phase II, single-arm, 48-week trial, the INHIBIT trial, to determine if Eloctate, begun before a bleed and continued as once weekly prophylaxis, will reduce inhibitor formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Whether or not Eloctate indeed promotes tolerogenicity is still not known and will be answered by the INHIBIT trial . Although none of the 165 patients enrolled in the phase 3 clinical trial using Eloctate developed an inhibitor, it is important to point out that these patients were more than 12 years old with no inhibitor history, and studies on previously untreated patients have not yet been published .…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not Eloctate indeed promotes tolerogenicity is still not known and will be answered by the INHIBIT trial . Although none of the 165 patients enrolled in the phase 3 clinical trial using Eloctate developed an inhibitor, it is important to point out that these patients were more than 12 years old with no inhibitor history, and studies on previously untreated patients have not yet been published .…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant cost and paucity of subjects available to conduct inhibitor prevention and eradication trials, the Working Group developed an estimate of the number of trials that could be supported within the HTC network (Table ). With approximately 1.82 severe haemophilia A PUPs born per year within the 141 US HTCs or approximately 257 per year, it is estimated only about 64 would qualify for a PUP prevention trial, with 75% disqualified for past factor, past bleed, refusal to participate in a trial, travel and time barriers, and competing trials . Thus, it is estimated up to 2‐3 PUP Inhibitor Prevention Trials utilizing novel design or embedded within registries could be supported within the HTC network.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is estimated up to 2‐3 PUP Inhibitor Prevention Trials utilizing novel design or embedded within registries could be supported within the HTC network. Approximately 10% of the severe haemophilia A population, or 1000, have inhibitors refractory to immune tolerance induction . Because they have such a poor response to treatment and are ineligible for gene therapy, it is anticipated such patients would be likely to enroll in an inhibitor eradication protocol.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that injury (bleeds/trauma) could be one of the risk factors for inhibitor development in HA patients. [41][42][43] In our preliminary studies, blood samples were collected from some of the platelet-infused animals (n 5 6) weekly by retro-orbital venous bleeds, which could represent a minor injury model. Notably, no anti-FVIII antibodies were detected in recipients during the entire study course of platelet infusion (data from early time points not shown).…”
Section: Discussionmentioning
confidence: 99%